Research on the Policy Effect of Property Tax Reform: Take the Pilot Reforms in Chongqing and Shanghai as Examples - Wei Dong; Xinqi Fu; Yang Zhang; Guowei Qin (Discrete Dynamics in Nature and Society)
It has been ten years since the implementation of property tax reform in Shanghai and Chongqing. With the continuous promotion of tax reform, the central government clearly put forward the decision to accelerate the pilot real estate tax reform in 2021. Every piece of news about the pilot and promotion of property tax reform attracts close attention from people in related fields and becomes a hot topic on the Internet and media. Reform policies are carefully formulated and improved, and the relationship between reform policies, market demand, and people’s livelihood is properly handled so that the real estate market will develop in a healthy and stable manner and have a significant impact on the economy and society. This article mainly starts with the history of property tax development, reform priorities, and comparison with property tax policies of other countries. It takes Chongqing and Shanghai as the research objects, selects several typical factors, and uses multiple linear regression models for analysis. This article studies the impact of China’s property tax pilot on the real estate industry and its effects from both theoretical and empirical aspects and discusses the policy effects of the property tax policy pilot. The levy of real estate tax has a certain effect in a short period of time, but it is not ideal in the long run. Studying the economic effects of Shanghai-Chongqing property tax is conducive to perfecting China’s property tax reform and promoting the healthy development of real estate market and economic and social development.